2005
DOI: 10.1002/jnr.20628
|View full text |Cite
|
Sign up to set email alerts
|

SIMPLE interacts with NEDD4 and TSG101: Evidence for a role in lysosomal sorting and implications for Charcot-Marie-Tooth disease

Abstract: Mutation of the SIMPLE gene (small integral membrane protein of the lysosome/late endosome) is the molecular basis of Charcot-Marie-Tooth disease type 1C (CMT1C), a demyelinating peripheral neuropathy. Although the precise function of SIMPLE is unknown, prior reports suggest it localizes to the lysosome/late endosome. Furthermore, murine Simple interacts with Nedd4 (neural precursor cell expressed, developmentally downregulated 4), an E3 ubiquitin ligase that is important for regulating lysosomal degradation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
88
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 30 publications
11
88
0
Order By: Relevance
“…Instead, SIMPLE is a substrate protein for degradation by the lysosome, as we can only detect the presence of SIMPLE in the lysosome and late endosome upon lysosome inhibition. Our finding that SIMPLE is an early endosomal membrane protein is consistent with the reported interaction of SIMPLE with the endosomal sorting complex required for transport (ESCRT) subunit TSG101 (Shirk et al, 2005) and suggests that SIMPLE regulates protein sorting at the early endosome.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Instead, SIMPLE is a substrate protein for degradation by the lysosome, as we can only detect the presence of SIMPLE in the lysosome and late endosome upon lysosome inhibition. Our finding that SIMPLE is an early endosomal membrane protein is consistent with the reported interaction of SIMPLE with the endosomal sorting complex required for transport (ESCRT) subunit TSG101 (Shirk et al, 2005) and suggests that SIMPLE regulates protein sorting at the early endosome.…”
Section: Discussionsupporting
confidence: 90%
“…First, mutation-induced mislocalization away from the early endosomal membrane would remove SIMPLE protein from its site of action, thereby contributing to CMT pathogenesis by a lossof-function mechanism (Kim et al, 2002;Lupo et al, 2009;Roberts et al, 2010). Although the cellular function of SIMPLE is unknown, it has been proposed that SIMPLE might participate in protein sorting at the early endosome (Shirk et al, 2005). Loss of endosomal function of SIMPLE triggered by CMT1C mutations might cause deregulated trafficking of myelin proteins and/or other membrane proteins, resulting in Schwann cell dysfunction and demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this ''classic'' route for protein breakdown, it is also known that ubiquitin regulates trafficking of proteins in the endocytic pathway. Monoubiquitinated proteins, most notably integral membrane proteins, are imported into multivesicular bodies (MVBs) and delivered to lysosomes for degradation (15,16). However, lysosomally degraded proteins are thought to be deubiquitinated before import into the lysosome.…”
Section: Resultsmentioning
confidence: 99%
“…In previous experiments demonstrating the transference of cytosolic cargo into lysosomes in macrophages infected with Leishmania, we found that this transfer was enhanced upon the induction of autophagy and was routed through autophagosomes, which appeared comparable ultrastructurally with MVBs (17). Moreover, cells deficient in autophagy accumulate aggregates of ubiquitinated proteins in the cytosol (16,18,19).…”
Section: Resultsmentioning
confidence: 99%
“…LITAF is predicted to encode a 161-amino-acid protein with distinct N and C termini (6). The N terminus of LITAF contains proline-rich binding domains for several cellular proteins, including neural precursor cell expressed, developmentally downregulate 4 (Nedd4) (3,7), tumor susceptibility gene 101 (TSG101) (8), and Itch (9), which function along a conserved pathway of lysosomal protein degradation. The C terminus of LITAF contains an arrangement of cysteine residues resembling a RING finger domain (4).…”
mentioning
confidence: 99%